2015
DOI: 10.3892/ijmm.2015.2250
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IGFBP-2 improves the sensitivity of bladder cancer cells to cisplatin via upregulating the expression of maspin

Abstract: The present study aimed to reveal the association between insulin-like growth factor binding protein-2 (IGFBP-2) and the sensitivity of bladder cancer cells to cisplatin, and determine the underlying mechanism involving maspin. A total of 32 bladder cancer tissue samples were collected for analysis. Cells of the BIU87 human bladder cancer cell line were cultured and a cisplatin-resistant subline (BIU87-CisR) was established by continuous exposure of the cells to cisplatin. Targeted inhibition of IGFBP-2 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Additional MTS and apoptosis assays revealed that ectopic maspin overexpressed in T24 (T24-Maspin) cells was more sensitive to cisplatin-induced apoptosis than mock-transfected T24 cells were (Figure 2E,F). These results are consistent with those of other studies reporting that the ectopic overexpression of maspin improved the sensitivity of bladder carcinoma cells to cisplatin [23,24]. Moreover, our study demonstrated that maspin blocked tumor growth in vivo when using xenografts of BALB/cAnN-Foxn1 NU mice (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
“…Additional MTS and apoptosis assays revealed that ectopic maspin overexpressed in T24 (T24-Maspin) cells was more sensitive to cisplatin-induced apoptosis than mock-transfected T24 cells were (Figure 2E,F). These results are consistent with those of other studies reporting that the ectopic overexpression of maspin improved the sensitivity of bladder carcinoma cells to cisplatin [23,24]. Moreover, our study demonstrated that maspin blocked tumor growth in vivo when using xenografts of BALB/cAnN-Foxn1 NU mice (Figure 4).…”
Section: Discussionsupporting
confidence: 93%
“…The overexpression of IGFBP2 has been reported to be responsible for tamoxifen resistance and recurrence in pre-menopausal women with ERα-positive breast cancer [ 27 ]. Inhibiting IGFBP2 improves the sensitivity of bladder cancer cells to cisplatin by elevating the expression of maspin [ 29 ]. However, no previous report has defined the relationship between IGFBP2 and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…All mouse experiments were approved by the Institutional Animal Care and Use Committee (IACUC), Taipei Medical University, and the methods used were in accordance with IACUC-approved guidelines. Five-week-old male Nu/Nu mice were used as the in vivo experimental model as described previously [ 28 , 29 ]. In brief, scrambled control and Hsp27-KD HepJ5 cells were suspended in PBS to a final density of 1 × 10 7 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, IGFBP2, has been reported as an oncogenic marker in various cancers including bladder cancer (36). It has been suggested that blockage of IGFBP2 may increase the sensitivity of bladder cancer cells to chemotherapy (37). SHBG modulates the bioavailability of sex hormones.…”
Section: Discussionmentioning
confidence: 99%